Professional football in Portugal: preparing to resume after the COVID-19 pandemic - Gouveia, C.; Pereira, R. (Soccer & Society, 2020)
This article offers a theoretical reflection on how the First Portuguese Football League is preparing to return to competition, after the suspension and mandatory confinement, as well as the security measures adopted in response to the pandemic caused by the new coronavirus. Despite the paper is descriptive and theoretical, our discussion draws particularly on documentary analysis of mass media/journalist reports, official almanacs, and academic works. A ?rst purpose of this paper, therefore, is to address the way in which professional football is financially exposed and vulnerable to the main sponsors, who seek to exert power and influence. Second, we seek to explore the increasing asymmetrical power relations of the broadcaster`s rights that are increasingly using strategies for wielding power than act a business partner. The implications arising from the study are considered for sport-governing bodies and clubs, in addition to future research directions.